Interleukin 1 Beta (IL1beta) Gene Polymorphisms (SNP-511 and SNP+3953) in Hashimoto’s Thyroiditis among the Polish Population - Lacka, K.; Paradowska-Gorycka, A.; Maciejewski, A.; Kramer, L.; Herman, W. A.; Lacki, J. K. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Aim: The association between the interleukin IL1 beta gene polymorphisms SNP-511 and SNP+3953 and susceptibility to the development of Hashimoto’s thyroiditis among adult Caucasian-Polish population were analyzed.Patients and methods: The group studied comprised of 115 unrelated patients with Hashimoto’s thyroiditis (112 women and 3 men, mean age 53.3 years). All patients were euthyroid on thyroid replacement therapy, had extremely high serum anti-TPO levels and in 53 patients anti-TG levels were also increased. The control group consisted of 103 healthy blood donors without raised anti-TPO antibodies, in whom a personal and familial history of thyroid, autoimmune and inflammatory diseases was excluded. No goiter or thyroid dysfunction was found.2 polymorphisms of the IL1 beta were studied by PCR-RFLP analysis. To confirm the accuracy of the method used, randomly selected patients were analyzed by direct sequencing.Results: In both groups allele frequencies were in Hardy-Weinberg equilibrium. The significant statistical differences between the frequency of C and T allele for both SNPs (C-511T and C+3953T) in the group studied and in the controls were found (p=0.0081; OR=1.846; 95% CI: 1.183–2.878 and p=0.0099; OR=1.953; 95% CI: 1.183–3.224).The frequencies of the genotype C-511C compared to C-511T and T-511T as well as C+3953C compared to C+3953T and T+3953T also differed significantly (p=0.0057; OR=2.248; 95% CI: 1.292–3.912 and p=0.0043; OR=2.338; 95% CI: 1.305–4.191) between patients and controls.Conclusions: An association between the SNPs of the IL1 beta and susceptibility to Hashimoto’s thyroiditis among the group of Caucasian-Polish population studied was found.
Keywords: Hashimoto’s thyroiditis; cytokines; SNP IL1 beta gene